Socioeconomic segregation of students - Prieto-Latorre, Claudia; Marcenaro-Gutiérrez, Óscar David; Vignoles, Anna (My University, 2019)
School segregation may be questioning the equity of the Spanish educational system. In this research, we analyse the school segregation by socioeconomic status using the Hutchens Index. Specifically, we decompose the effect of attending public vs semiprivate schools in terms of segregation. The analyses is based on data collecting information from the population of Andalusian students attending 5th grade. We found significant differences in the level of segregation between both schools types. Particularly, the results show that students from high socioeconomic and cultural status are more segregated in public schools, while students from a low socioeconomic and cultural status are more segregated in semiprivate schools. These differences provide evidence of the inequity of the education policy, which should rethink funding mechanisms as a means to fight against inequality.
Keywords: Segregación en educación; Escuelas públicas; Socioeconomic level; Semiprivate schools; Hutchens Index